2022
DOI: 10.1007/s00296-022-05140-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different protocols of physical exercise on fibromyalgia syndrome treatment: systematic review and meta-analysis of randomized controlled trials

Abstract: Physical exercise has been used as a form of treatment for fibromyalgia, however, the results indicate the need for further investigations on the effect of exercise on different symptoms. The aim of the study was to synthesize and analyse studies related to the effect of exercise in individuals with fibromyalgia and provide practical recommendations for practitioners and exercise professionals. A search was carried out in the Web of Science, PubMed, and Scopus databases in search of randomized clinical trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 68 publications
2
40
0
Order By: Relevance
“…The results of another recent metaanalysis show that especially resistance exercises are effective on pain and fatigue in patients with FMS (34). In addition, in terms of physical exercise intensity, it has been reported that the exercise intensity should be light at the beginning and increased over time to not aggravate the symptoms of FMS patients (10). The results of this study showed that the kinesiophobia levels of FMS patients were high.…”
Section: N Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The results of another recent metaanalysis show that especially resistance exercises are effective on pain and fatigue in patients with FMS (34). In addition, in terms of physical exercise intensity, it has been reported that the exercise intensity should be light at the beginning and increased over time to not aggravate the symptoms of FMS patients (10). The results of this study showed that the kinesiophobia levels of FMS patients were high.…”
Section: N Discussionmentioning
confidence: 56%
“…On the other hand, Sieczkowska et al showed that physically active patients with FMS had better quality of life and less depressive symptoms (28). In a recent meta-analysis, it has been reported that the intervention of physical exercises was effective on the symptoms and physical well-being of FMS patients (10). The results of another recent metaanalysis show that especially resistance exercises are effective on pain and fatigue in patients with FMS (34).…”
Section: N Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommendation for exercise is due to its ability to increase slow-wave sleep, which helps thermoregulation (Youngstedt, 2005), alters the circadian cycle and alters levels of neuropeptides and neurotransmitters in the brain that play important roles in sleep (Buman and King, 2010). Furthermore, exercise has shown to improve general health, symptoms of the disease and physical function (Busch et al, 2011) and in general, the recommendations are aimed at aerobic exercise and resistance training (RT) (Albuquerque et al, 2022; Macfarlane et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, aerobic exercise can improve the quality of life and relieve muscle pain in FMS (Busch et al, 2007 ), while resistance exercise can significantly improve physical function in FMS (Busch et al, 2013 ). However, most current clinical studies only analyze the efficacy of two exercise programs by comparing each other (Rooks et al, 2007 ; Alentorn-Geli et al, 2008 ), and most meta-analyses start with only a few outcome indicators, for example, quality of life, fatigue, and sleep quality (Estévez-López et al, 2021 ; Albuquerque et al, 2022 ). The extant studies lack a comparison of the three common exercise programs from the three perspectives of improving quality of life, relieving muscle pain, and simultaneously enhancing physical function in patients with fibromyalgia.…”
Section: Introductionmentioning
confidence: 99%